Answer:
C is not a zero for the solution of the polynomial equation
Please slow down with posting questions, this seems like a Canvas Exam.
let "a number" = x
(x) + (x + 1) + (x + 2) = 72
Simplify. Combine like terms
3x + 3 = 72
Isolate the x. Note the equal sign. What you do to one side, you do to the other. Do the opposite of PEMDAS.
3x + 3 (-3) = 72 (-3)
3x = 72 - 3
3x = 69
3x/3 = 69/3
x = 69/3
x = 23
23 is the smallest number
hope this helps
Answer:
1) -15/32
2) 2/15
3) -203.5
4) -3/2 = -1.5
5) 10/3 = 3 1/3
Step-by-step explanation:
For 1, you just multiply the numerators and denominators together (3 by 5, 4 by 8) and then because it is negative, add the negative sign.
For 2, you multiply again, but because there are 2 negative signs, it becomes positive.
For 3, you divide 81.4 by 0.4, you could also divide 814 by 4.
For 4, you keep change flip, so the equation would become -9/4 (-2 1/4=-9/4) and 3/2 would become 2/3. The equation would be (-9/4 * 2/3). Then, you would get -18/12 which is -3/2.
For 5, you just multiply 4/3 by 5/2 which is 20/6 and because 2 negatives, it becomes positive.
2ways you can solve that is by multiplying 9 by 1 then by 5 or 9by 5 then by 1
Answer:
name as AB =CD
angle A=angle D
BC=BC
hence angle ABC is congruent to angle BCD
(by sas congruency)
hence proved